InvestigaÃÃo farmacolÃgica dos mecanismos de aÃÃo gastroenteroprotetores do Ãcido CentipÃdico, um diterpeno de Egletes Viscosa Less., em modelos experientais - Marjorie Moreira Guedes (2010)
Pharmacological investigations on the mechanisms of gastroenteroprotective of centipedic acid, a diterpene from Egletes viscosa Less. in experimental models. Author: Marjorie Moreira Guedes. Advisor: Prof. Dr. Vietla Satyanarayana Rao. Doctoral thesis. Post-Graduate Program in Medical Science. Departamento of Clinic Medicine, UFC, 2008. Centipedic Acid (CA), a diterpene isolated from Egletes viscosa Less. (Asteraceae) was evaluated in experimental models of acute and chronic gastric injury and intestinal injury. CA (50 and 100mg/kg, po) significantly attenuated the gastric lesions induced by ethano. In the mechanistic study, (CA 50 mg/kg) its gastroprotection was shown to involve nitric oxide, prostaglandins, potassium channels ATP-dependent, but not TRPV1 receptors. The diterpene was able to decrease significantly the ethanol associated depletion of NP-SH and SOD levels, and increased MDA formation. Besides, CA enhanced the gastric mucus significantly. In the model of acidified ethanol orally administreted CA (50 and 100mg/kg, po) and lansoprazol (30mg/kg po) markedely attenuated the gastric lesions. In this model, the combination of AC (50 mg/kg) with lansoprazole (30 mg/kg) showed the potentiation on their effects. In the study of action mechanism, CA shown involvement of opioid receptors and α2-adrenergic receptors. CA (50 mg/kg po) decreased significantly the secretory volume and gastric acidity but failed to modify the gastric emptying in rats. CA (7.9, 15.8 e 31.6 mM) did not demonstrate anti-Helicobacter pylori activity in vitro. In the model of chronic gastric ulcer induced by acetic acid, CA (50 mg/kg po) decreased significantly the injured area as much as in 7 to 14 days of treatment. The histological findings evidenced greater fibroblastic activity in the group treated with CA, indicating that it aids in healing process as judged from the recorded parameters of hemorrhage, edema, congestion, exfoliation, infiltration, necrosis and angiogenesis. In the model of intestinal ulcers induced by indomethacin (10mg/kg po) for three days, no changes in the kidneys function (urea and creatinine) or liver enzymes (AST and ALT) were observed. CA (50mg/kg) treatment decreased significantly the number of longitudinal ulcers (>5mm), but not the number of pointed ulcers (<5mm). CA demonstrated an antioxidant effect by reducing the levels of MDA and MPO and by restoring the levels of NP-SH and catalase activity. In intestinal cells (IEC-6) culture, CA (12.5, 25, 50 and 100 μM) showed pro-migratory action, and its association (25, 50 and 100μM) with 250 μM indomethacin, but not with 1000 μM, mitigated the toxicity of indomethacin. CA (6.25, 12.5, 25, 50, 100 and 200 μM) alone showed no statistical difference on cell proliferation of IEC-6. However, in association, CA (12.5, 25, 50, 100 mM) significantly protected the IEC-6 cells from indomethacin (250 and 1000 μM) toxicity. These data suggest that CA diterpene has the gastroenteroprotective potential possibly related to an antioxidant mechanism and it could be an effective therapeutic agent for the treatment of gastrointestinal ulcerations and side effects to NSAIDs. .